THEORETICAL ASPECTS OF PEDAGOGICAL RESEARCH METHODS AND STATISTICAL HYPOTHESES (Scientific journal of the Fergana State University, 2024)
The article discusses the methods of pedagogical research, methods of experimentation, the concept of hypothesis, the issues of statistical hypothesis theory, the concepts of the distribution of the random amount observed in the experiment.